2000
DOI: 10.1128/jb.182.21.6066-6074.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the Genome of the Temperate, Serotype-Converting, Pseudomonas aeruginosa Bacteriophage D3

Abstract: Temperate bacteriophage D3, a member of the virus family Siphoviridae, is responsible for serotype conversion in its host, Pseudomonas aeruginosa. The complete sequence of the double-stranded DNA genome has been determined. The 56,426 bp contains 90 putative open reading frames (ORFs) and four genes specifying tRNAs. The latter are specific for methionine (AUG), glycine (GGA), asparagine (AAC), and threonine (ACA). The tRNAs may function in the translation of certain highly expressed proteins from this relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 78 publications
(57 reference statements)
1
77
0
1
Order By: Relevance
“…Preliminary experiments suggested that unlike those in other phages (23,41,82), the attPPЈ site might not be located close to the int gene (unpublished data). An excisionase-encoding gene (xis) was not identified in either the PH15 or CNPH82 genome, similar to the case for other phages where the xis gene is absent but an int gene is predicted (23,32,82).…”
Section: Resultsmentioning
confidence: 88%
“…Preliminary experiments suggested that unlike those in other phages (23,41,82), the attPPЈ site might not be located close to the int gene (unpublished data). An excisionase-encoding gene (xis) was not identified in either the PH15 or CNPH82 genome, similar to the case for other phages where the xis gene is absent but an int gene is predicted (23,32,82).…”
Section: Resultsmentioning
confidence: 88%
“…It has been involved in serotype conversion of its lysogenic host by changing the O-antigenic polysaccharide side chain of the lipopolysaccharide. An O-acetylase responsible for part of the seroconversion was located on phage D3 upstream of the lysis cassette (107). D3 shows a genome organization characteristic of lambda-like coliphages, except that the lysis module has changed its position.…”
Section: Opportunistic Pathogens and Free-living Bacteriamentioning
confidence: 99%
“…Plasmid pPMA4326A does not appear to encode any identifiable virulence genes, but it does possess several putative transposases. ORFs A09 and A10 appear to constitute an IS3-like element that is most closely related to IS222 from the D3 bacteriophage of Pseudomonas aeruginosa (49), and ORF A17 encodes an IS1406 transposase of the IS5 family. The putative borders of both IS elements encompass only their respective transposases.…”
Section: Resultsmentioning
confidence: 99%